Sol Electrolyte: Pathway to Long‐Term Stable Lithium Metal Anode - Sun, Chuang; Dong, Jing; Lu, Xidi; Li, Yinwei; Lai, Chao (Advanced functional materials, 2021)
Lithium (Li) metal batteries are the subject of intense study due to their high energy densities. However, uncontrolled dendrite growth and the resulting pulverization of Li foil during the repeated plating/stripping process seriously diminish their cycling life. Herein, a facile approach using octaphenyl polyoxyethylene (OP‐10)‐based sol electrolyte is proposed to alleviate Li anode pulverization. This sol electrolyte possesses better ionic conductivity compared to gel and solid‐state electrolytes and also homogenizes Li ion diffusion throughout the entire electrolyte efficiently. As a result, Li/Li symmetric cells using this sol electrolyte demonstrate long‐term cycling stability for up to 1800 h, with a plating capacity of 3.0 mAh cm−2 without deteriorating the integrity of the thin Li foil. Using a conventional liquid electrolyte, electrode pulverization and battery failure can be observed after just three cycles. More importantly, a parameter of “throwing power” is introduced in a metal Li battery system to characterize the homogenizing ability of Li deposition in different electrolyte systems, which can serve as a guide to the efficient selection of electrolytes for Li metal batteries. A liquid sol electrolyte is proposed as an alternative to a gel or solid‐state electrolyte to significantly alleviate the pulverization of Li anode without changing the production process of existing commercial batteries. Uniform and dense deposition, accompanied by robust solid electrolyte interphase films ensure the long‐term cycling stability of Li anodes even at a high plating capacity of 3 mAh cm−2.